To simplify the expression \(\frac{10 j^{-3}}{-2 (j^{-3})^3}\), we will follow these steps:
-
Simplify the denominator: \[ -2 (j^{-3})^3 = -2 j^{-9} \] This is because when you raise a power to another power, you multiply the exponents: \((-3) \cdot 3 = -9\).
-
Rewrite the fraction: So, we rewrite the fraction: \[ \frac{10 j^{-3}}{-2 j^{-9}} \]
-
Divide the numerical coefficients: The numerical part is: \[ \frac{10}{-2} = -5 \]
-
Divide the variable parts (using the property \(\frac{a^m}{a^n} = a^{m-n}\)): For the variable part, we have: \[ \frac{j^{-3}}{j^{-9}} = j^{-3 - (-9)} = j^{-3 + 9} = j^{6} \]
-
Combine the results: Therefore, the expression simplifies to: \[ -5 j^{6} \]
-
Express in positive exponents: Since the original expression does not have any negative base after simplification, we keep it as is.
So, the final result in simplest form using only positive exponents is: \[ -5 j^{6} \]